Penerapan Media Pembelajaran Gamifikasi Wordwall Terhadap Hasil Belajar Pada Tema Benda Hewan dan Tanaman Kelas 1 SD Negeri 101911 Sidodadi Batu 8 Deli Serdang - Tri Yuli Hardeliska; Ahmad Landong (Jurnal Dirosah Islamiyah, 2023)
This study aims to determine 1) the effect of the aplication of wordwall gamificationlearning media on the learning outcomes of the theme of object, animals and plants of grade 1 student of SD Negeri 101911 Sidodadi Batu8 Deeli Serdang, 2) the improvement of learning outcomes of the theme of object, animals and plants of grade 1 student of SD Negeri 101911 Sidodadi Batu8 Deeli Serdang by using wordwall gamification media. The research method use was classroom action research The subject of the study was grade 1 elementary school students totaling 26 students. Data collection techniques in this study use test techniques. The research instrument is in the form of an observation sheet. The result showed that there was an increase in learning outcomes after the application of wordwall gamification learning media was shown by the increase that accurred after the research was carried out. This proven by the average grade score of 71,1 out of 26 students, only 12 students or around 46,1% of students who managed to reach the standars of completeness in the pre-cycle stage to an average grade score of 73,4 wit 42,3% of student completing in the first cycle. In cycle 2, the grade point avarage became 78,4 with 65,4% of students complete. In cycle 3, the grade point avarage became 85 with 84.6% of students complete. And it can be concluded that the application of wordwall gamification learning media to student learning outcomes on the theme object, animals and plants in grade 1 SD Negeri 101911 Sidodadi Batu8 Deli Serdang can effect student learning outcomes and there is also an increase in learning outcomes. Keywords : wordwall gamification learning media, learning outcomes, classroom action research.